PRINSCIPLES OF MATERIALS DEVELOPMENT FOR ESP TRAINING COURSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article analyzes the principles of developing educational materials in English based on domestic and foreign experience. It is illustrated how each of the principles was implemented when creating a training course for university teachers and graduate students. It is concluded that it is necessary to consider modern methodological approaches when creating a new generation textbook that meets the requirements of the modern paradigm of education.